2015
DOI: 10.1103/physrevc.91.024304
|View full text |Cite
|
Sign up to set email alerts
|

Helium-helium clustering states inBe12

Abstract: An inelastic excitation experiment was performed with a 12 Be beam at 29 MeV/u on a carbon target. New resonances close to the respective cluster separation thresholds were observed in 12 Be for the 4 He + 8 He and 6 He + 6 He decay channels, confirming the previously proposed molecular rotational bands. Using the model-independent angular correlation analysis, a 0 + spin parity is assigned to the remarkably large peak at 10.3 MeV in the 4 He + 8 He channel. A distorted wave Born approximation (DWBA) calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 68 publications
(191 reference statements)
1
23
0
Order By: Relevance
“…The obtained pairing function is similar to that in Ref. 10 where the Fermi level is far below the vHS, suggesting the robustness of this type of pairing symmetry. Indeed, similar results are obtained for n = 0.61, corresponding to the top line in Fig.1(a), with U = 1.6 eV, J H = 0.4U and V = 0, although the Fermi level is slightly above the vHS and the Fermi pockets now concentrate on the M points, see the inset in Fig.3(b).…”
Section: Sm-frgsupporting
confidence: 85%
See 2 more Smart Citations
“…The obtained pairing function is similar to that in Ref. 10 where the Fermi level is far below the vHS, suggesting the robustness of this type of pairing symmetry. Indeed, similar results are obtained for n = 0.61, corresponding to the top line in Fig.1(a), with U = 1.6 eV, J H = 0.4U and V = 0, although the Fermi level is slightly above the vHS and the Fermi pockets now concentrate on the M points, see the inset in Fig.3(b).…”
Section: Sm-frgsupporting
confidence: 85%
“…According to first principle calculation, 8-10 the band electrons near the Fermi level are mainly derived from the x-and y-orbitals of Bi. A corresponding tight-binding model can be written as [8][9][10]18 ,…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The two peaks at 2360 and 2340 cm À 1 , seen in all three spectra, are characteristic for physisorbed CO 2 [67] that is either present as decomposition product of the solution components during the spraying process, or arising from adsorbed CO 2 on the sample's surface, as it is exposed to the air. Since this peak is not present for the pure glass substrate, it is concluded that the presence of CO 2 arises from the spraying process.…”
Section: Optical and Electrical Properties Of Sprayed Cu 2 O Filmsmentioning
confidence: 90%
“…The relative energy (E rel ) of the decay fragments 10 Be + α can be calculated from their kinetic energies (T a , T b ) and the opening angle θ, according to the invariant mass (IM) method [24], which takes part in the excitation energy E x :…”
Section: Observed Resonances and Discussionmentioning
confidence: 99%